Assessment of four main representative flint facies as alternative storage materials for concentrated solar power plants. (June 2019) - Nahhas, Tamar; Py, Xavier; Sadiki, Najim; Gregoire, Sophie
Highlights: Natural alternative storage material for sensible heat storage in concentrated solar power plants. Assessment of flint rocks as low-cost storage materials in thermocline storage system. Complete study of physical and mechanical behavior of flint under thermal cycles from room temperature up to 400 °C. Flint shows thermal stability up to 400 °C and good physical and mechanical properties. Abstract: At present there is an intense research for developing alternative sensible heat storage materials, such as natural rocks and recycled ceramics, able to work in concentrated solar power plants at high temperatures. This work demonstrates the potential of flint rocks as an economic and efficient filler material to be used with air as heat transfer fluid in packed bed storage system. Four facies of flint rocks were collected from south of France. To predict the performance of the storage system, crystalline structure, thermo-physical and thermo-mechanical properties of the studied rocks have been identified. For this purpose, the candidate rocks were subjected to extensive experimental characterizations under a series of thermal cycles. XRD, SEM, DSC/TGA, pycnometer, LFA, dilatometer, high temperature ultrasonic testing and nano-indenter method have been used to analyze these samples. Consequently, the 400 °C was identified as ideal temperature for the heat treatment process of flint. The obtained results from the four analyzed samples have been compared together and with currently used storage materials. The results gathered from this paper prove the potential of flint in terms of high density, good specific heat capacity and good thermal stability up to 400 °C to be used as filler material in energy storage applications relevant for low and medium temperature solar power plants.